Readymade grammar. Why are Finnish postpositions an open class? - Jaakola Minna; Ojutkangas Krista (Suomalaisen Kirjallisuuden Seura, 2026)
Postpositions relate to the local case system both semantically and
structurally: they share the basic semantic categories they express, and the
majority of Finnish postpositions are lexicalised forms of nouns inflected in
local cases. This paper focuses on Finnish postpositions as open class. Finnish
postpositions form sets, that is, groups of words that have different lexical
origins but with near-synonymous meanings and similar morphological
structures. The sheer number of Finnish postpositions makes it implausible
that each of them would have undergone an individual grammaticalisation
process. The objective of this study is to evaluate the emergence of new
postpositions from a wider perspective, relying on construction-based
argumentation. A crucial factor in the openness of postpositions is the
ambiguity of the genitive construction, which makes it possible to reanalyse
a local-case inflected noun as a postposition, and to begin using it in a
postposition construction. This is how some postposition types acquire
new members directly as readymade postpositions. These are lexemes in a
local case form which become postpositions by entrenchment, by repeated
use of language speakers. This analysis introduces several mechanisms of
entrenchment that produce and maintain openness. The basic mechanism is
analogy, and the analysis also points to different motivations that explain the
postposition sets: language users seek out expressions for different semantic
nuances, and they look for novel or even playful expressions. However, other
motivating factors are language ideologies and the impact of other languages.
The Finnish Case System. Cognitive Linguistic Perspectives